Antioxidant and antiproliferative activities of six Malaysian medicinal plants and mechanism of action through microrna in thyroid cell lines - Ismail, Aziana (2019)
Thyroid cancers, including papillary, follicular, medullary and anaplastic carcinomas, have different growth rates and can metastasize if left untreated. Even though most thyroid cancer cases have good prognosis, the risk of recurrence among the patients is high and some patients die from progressive tumor. Medicinal plants are commonly used as alternative to cancer treatment in many countries. The antiproliferative activity of phytochemicals has been demonstrated in various cancers, yet the effect of medicinal plants on thyroid cancer remain under-investigated. Despite various reports on the anti-cancer activities of plant extracts on a variety of cancer cell lines, the cellular targets and the underlying mechanisms remain unclear. The overall goal of the present study was to investigate the effect of crude extracts from six medicinal plants (Annona muricata L., Angelica keiskei Ito, Chromolaena odorata (L.) R.M.King & H. Rob, Clinacanthus nutans (Burm. f.) Lindau, Euphorbia hirta L., and Leea indica (Burm. f.) Merr.) on thyroid cell lines (Nthy-ori 3-1, FTC-133 and Hth- 74) and the mechanism involved. For antioxidant and anti-proliferative activities of the plant extracts, methods such as Folin-Ciocalteu’s, aluminum chloride, DPPH free radical scavenging assays and MTT assay were utilized. Flow cytometric analysis of treated cells stained with propidium iodide and with Annexin V-FITC/propidium iodide, and TUNEL assay further confirmed the anti-proliferative activity of the plant extract. Quantitative real-time RT-PCR of apoptotic related genes, candidate microRNAs and their putative target genes were also performed. Methanolic extract of E. hirta had high amount of total phenolic and flavonoid contents at 307.59 ± 3.57 mg GAE/g dw and 76.43 ± 4.34 mg QE/g dw, respectively. The extract had 32% of DPPH scavenging with IC50 of 0.013 mg/mL. Significant reduction of cell viability was observed when treated with A. muricata and C. odorata methanolic extracts with IC50 of 20.8 and 74.9 mg/mL in FTC-133 cells at 72 hours of treatment. FTC-133 cells treated with A. muricata methanolic extract showed significant increase in percentage of cells at the S- and G2/M-phase with subsequent significant decrease in G0/G1-phase. Flow cytometric analysis of cells treated with Annexin V-FITC/propidium iodide and analysis of TUNEL assay further confirmed that A. muricata methanolic extract induced apoptosis in FTC-133 cells. Gene expression analysis of apoptosis-related genes suggest that intrinsic apoptosis pathway was induced by the significant increase in expression of pro-apoptotic gene, BAX and significant decrease in expression of anti-apoptotic gene, BCL2. In addition, significant reduction in the expression of several microRNAs (miR-192, miR-197, miR-328 and miR-346) in FTC-133 cells treated with A. muricata methanolic extract suggest for potential underlying mechanism of the anti-proliferative property. In conclusion, large amount of phenolic and flavonoid compounds in E. hirta contributed to its high antioxidant activity. Treatment of A. muricata methanolic extract resulted in significant anti-proliferative activity in FTC-133 cells through cell cycle arrest and induction of apoptosis. The antiproliferative activity may also be due to modulation of several microRNAs aberrantly expressed in FTC-133 cells. The potential of A. muricata methanolic extract in the prevention of thyroid cancer development focusing on the microRNAs regulation pathway should be further investigated.